Gender and Academic Program Differences in Metacognitive Online Reading Strategies Among EFL University Students - Nur Annisa Fitri; Selvi Selvi; Rifqi Pratama; Dewi Wijaya Putri; Hafiz Anshari; Intan Nuraini; Abdul Syahid (Jurnal Ilmiah Profesi Pendidikan, 2026)
Metacognitive online reading strategies are essential for helping English as a Foreign Language (EFL) students comprehend digital texts in higher education. However, studies investigating differences in these strategies based on gender and academic program among Indonesian EFL students remain limited. This study aimed to investigate the metacognitive online reading strategies employed by EFL students and examine whether significant differences existed based on gender and academic program. This study employed a descriptive quantitative survey design using a 15-item adapted version of the Online Survey of Reading Strategies (OSORS). The instrument demonstrated high reliability (Cronbach's Alpha = .892). A total of 223 students (51 males and 172 females) from eight study programs participated in the study. Data were analyzed using descriptive statistics, the Mann-Whitney U test, and the Kruskal-Wallis H test. The findings revealed that Problem-Solving Strategies were the most frequently used (M = 4.14), followed by Global Strategies (M = 3.90) and Support Strategies (M = 3.80), all classified as high-use strategies. Significant gender differences were found in Problem-Solving Strategies (U = 3567, p = .042) and Support Strategies (U = 3343, p = .010), with female students demonstrating higher strategy use, whereas no significant difference was found for Global Strategies. Furthermore, no significant differences were identified among the eight academic programs for any strategy category (p > .05). In conclusion, metacognitive online reading strategies are influenced by gender but not by academic program, indicating that these strategies function as general academic literacy skills across disciplines. These findings support the integration of metacognitive reading strategy instruction into EFL higher education to enhance students' digital reading competence.